Consumer Trust in Mediating the Influence of Brand Image and Celebrity Endorse on Purchase Decisions - Fatma Qori Amalia; Muhammad Shofiyuddin (Sean Institute, 2025)
This research was conducted on the Kazami Brand, with a sample of 50 Kazami consumer respondents and processed using SEM SmartPLS 4.0. The results of the research show that there is a significant influence of brand image on purchasing decisions, there is a significant influence of celebrity endorsers on purchasing decisions, there is a significant influence of brand image on consumer trust, there is a significant influence of celebrity endorsers on consumer trust, there is a significant influence of consumer trust on purchasing decisions, there is a significant influence of consumer trustin mediating the influence of brand image on purchasing decisions, there is a significant influence of consumer trust in mediating the influence of celebrity endorsers on purchasing decisions for Kazami products.